Pemberdayaan Masyarakat Melalui Program dan Layanan Penguatan Kelembagaan dari Ruang Belajar Aqil: Studi pada Kampung Cerdas Ceria Galeri Kreatif - Faradilla Aghnia Alifia; Sonja Andarini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education plays a pivotal role in shaping human lives and provides a foundation for positive change. However, the lack of parental guidance in accessing education poses a challenge that needs to be addressed. Ruang Belajar Aqil, as a local education initiative, emerges as the optimal solution to enhance self-capacity through learning assistance and community empowerment. This study employs a qualitative method with a descriptive approach, aiming to understand and analyze the process of community empowerment through programs and institutional strengthening services provided by Ruang Belajar Aqil in Kampung Cerdas Ceria (KCC) Galeri Kreatif. Empowerment indicators are delineated through stages of activities, namely the Location Selection Stage, Community Empowerment Socialization Stage, Community Empowerment Stage, and Community Self-Reliance Stage, in accordance with the theoretical concept of community empowerment. This research contributes valuable insights into community empowerment efforts through Ruang Belajar Aqil, opening possibilities for improvements in the education system and empowerment of the local community.